Effect of tropical climate on performance during repeated jump-and-reach tests - Hue, O.; Coman, F.; Blonc, S.; Hertogh, C. (The Journal of Sports Medicine and Physical Fitness, 2003)
The aim of the present study was to determine the effect of tropical climate (i.e., hot and humid) on performance during multiple jump-and-reach tests. Methods. Fourteen male basketball players volunteered to perform two randomized series of jump-and-reach tests, which consisted of a jump-and-reach test every 15 s for 5 min (21 jump-and-reach tests) in two thermal conditions: tropical (TR, 30.4 °C, 70 % rh) and thermoneutral (TN, 23.1 °C, 53 % rh). During each test, lactate concentration [La-], tympanic temperature (Tty), sweat rate (SR), heart rate (HR), and performance (height: H) were noted at rest, during exercise and recovery. Two hours of recovery separated the TN and TR tests. Results. There were no significant differences in mean height, maximal height or the kinetics between TN and TR. Both conditions induced an increase in height over time (time effect: P < 0.002). There were no significant differences in [La-] at rest or during exercise or recovery in the two conditions. Both conditions induced an increase in [La-] (time effect: P < 0.002). There was a tendency toward a higher mean [La-] during TR than TN (situation effect, P < 0.07). However, compared to resting values, [La-] values were significantly increased only in TR and not in TN. Tty, was significantly greater (P < 0.001) at rest and during exercise and recovery in TR than in TN. SR and HR were also significantly greater at rest and during exercise and recovery in TR TN (P < 0.001 for SR and HR). Conclusion. We conclude that tropical climate affects physiological responses without improving or decreasing performance during successive jump tests.